The fears are mine imprison me and ...? (Journal of Parents and Teachers, 2014)
This article has four different situations and its activities to work with fear from four different points of view, but related to making decisions in different moments of life: adolescence, partnership, work and family.
Keywords: fear; monographic about fear; defense; getting over fears.